Religious-based ethics and buy-now-pay-later re-usage intention among Muslim consumers in Indonesia and Malaysia: a commitment-trust theory perspective - Hendy Mustiko Aji; Maizaitulaidawati Md Husin; Abdul Kadir Othman; Anas Hidayat; Wan Edura Wan Rashid (Cogent Business & Management, 2024)
This study investigates the effect of religious-based ethics (knowledge about riba and perceived riba risk) on Buy-Now-Pay-Later (BNPL) re-usage intention among Muslim consumers in Indonesia and Malaysia from the lens of commitment-trust theory. An online survey was conducted among 434 adult Muslims in Indonesia and Malaysia who self-reported BNPL usage. The model was analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. Our study shows that religious-based ethics can discourage BNPL re-usage intention, but only when commitment is low, highlighting its mediating role. Interestingly, our study found no significant connection between trust in BNPL and its re-usage intention. These findings hold for both countries, except for the relationship between riba knowledge and trust, which was only significant in Indonesia. This study is the first to examine religious-based ethics within the BNPL context using commitment-trust theory.
Keywords: 650; riba knowledge; riba risk; commitment; trust; re-intention; buy-now-pay-later